Effect of soil management and of crop rotation systems on wheat yield and diseases - dos Santos, Henrique Pereira; Lhamby, Julio Cesar Barreneche; Prestes, Ariano Moraes; de Lima, Marcos Roberto (Pesquisa Agropecuaria Brasileira, 2000)
The effects of soil management systems and winter crop rotation on wheat yield and root diseases were assessed. No-tillage, minimum tillage, conventional tillage using a disc plow plus disc harrow, and tillage using a moldboard plow plus disc harrow were the soil managements compared. In crop rotation, three systems were used:system I (wheat/soybean), system II (wheat/soybean and common vetch/corn or sorghum), and system III (wheat/soybean, black oats or white oats/soybean, and common vetch/corn or sorghum). A randomized block experimental design, with split-plots and three replicates, was used. The main plots were formed by the soil management systems, while the split-plots consisted of crop rotation systems. Yield of wheat grown under no-tillage and minimum tillage was higher than the yield of wheat grown under conventional soil tillage using either disc plow or moldboard plow. Crop rotation was efficient in reducing root diseases and in increasing wheat yield.